The Origins of Paronyan’s Fairy Tales and Their Types (Conte genre) - Makaryan, Albert (Bulletin of Yerevan University B: Philology, 2022)
The article is dedicated to Hakob Paronyan’s works intended for children. Here the author’s fairy tales, the art of their construction, the logic and origins of choosing a model were considered, and according to all these, the author’s worldview is also studied. As in the works addressed to the adults likewise in the context of the children’s literature, the satirist writer prefers realistic fiction regularly and consistently providing children with works responsive to real life. But in the case of fairy tales entitled “Karmir Varduk (“The Red Riding Hood”)” and “The Ring of Giges” the author deviates from his drawn line by building in the first case a model of a terrible miracle, while in the second case he decomposes the above mentioned model and breaks the faith in it.The article is dedicated to Hakob Paronyan’s works intended for children. Here the author’s fairy tales, the art of their construction, the logic and origins of choosing a model were considered, and according to all these, the author’s worldview is also studied. As in the works addressed to the adults likewise in the context of the children’s literature, the satirist writer prefers realistic fiction regularly and consistently providing children with works responsive to real life. But in the case of fairy tales entitled “Karmir Varduk (“The Red Riding Hood”)” and “The Ring of Giges” the author deviates from his drawn line by building in the first case a model of a terrible miracle, while in the second case he decomposes the above mentioned model and breaks the faith in it.